Insights into the pigment and non-pigment phenolic profile of polyphenol extracts of jujube peel and their antioxidant and lipid-lowering activities. (April 2023) - Dou, Jin-Feng; Wu, Cai-E; Fan, Gong-Jian; Li, Ting-Ting; Li, Xiao-Jing; Zhou, Dan-Dan; Zhu, Jin-Peng; Li, Chun-Mei
Abstract: This study aimed to provide a comprehensive overview of the pigment and non-pigment phenolic profile of polyphenol extracts of jujube peel and their bioactivities. Firstly, the pigment and non-pigment phenolic composition as well as antioxidant activities of free and bound polyphenol extracts in jujube peel were compared among twelve varieties systematically. Then the antioxidant and lipid-lowering activities of free and bound polyphenol extracts of 'Junzao' jujube peel were investigated representatively. Overall, 23 phenolic compounds were identified, in which flavonols were the main pigments and all varieties showed similar qualitative patterns but different quantitative characteristics. The antioxidant activities significantly correlated with the content of total phenolics and total flavonoids. Furtherly, both free and bound polyphenol extracts of 'Junzao' jujube peel exhibited DPPH, ABTS free radical scavenging capacity, and oxygen radical absorbance capacity in a dose-dependent manner. Besides, both of them improved the resistance of Caenorhabditis elegans under H2 O2 oxidative stress and heat stress at 37 °C (20–100 μg/mL). What's more, compared to free polyphenol extract, bound polyphenol extract decreased the level of body lipid accumulation and triglyceride more effectively. These results suggest that jujube peel is an exploitable source of natural flavonoid pigments and phenolic ingredients with strong antioxidant and lipid-lowering properties. Highlights: The pigment and non-pigment phenolic profile of jujube peel were analyzed. FPEJZ and BPEJZ have potent antioxidant activities in vitro and in vivo . FPEJZ and BPEJZ of could reduce intracellular ROS levels in C. elegans. BPEJZ showed better antioxidant and lipid-lowering activities than FPEJZ . The information may be useful for jujube peel as functional food ingredients.